Recovery of terbium by Lysinibacillus sp. DW018 isolated from ionic rare earth tailings based on microbial induced calcium carbonate precipitation - Bian, Zijun; Dong, Wei; Ning, Zhoushen; Song, Yuexin; Hu, Kaijian (Frontiers in Microbiology, 2024)
Microbial induced calcium carbonate precipitation (MICP) is considered as an environmentally friendly microbial-based technique to remove heavy metals. However, its application in removal and recovery of rare earth from wastewaters remains limited and the process is still less understood. In this study, a urease-producing bacterial strain DW018 was isolated from the ionic rare earth tailings and identified as Lysinibacillus based on 16S rRNA gene sequencing. Its ability and possible mechanism to recover terbium was investigated by using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and fourier transform infrared spectroscopy (FTIR). The results showed that the urease activity of DW018 could meet the biomineralization requirements for the recovery of Tb 3+ from wastewaters. The recovery rate was as high as 98.28% after 10 min of treatment. The optimal conditions for mineralization and recovery were determined as a bacterial concentration of OD600 = 1.0, a temperature range of 35 to 40 °C, and a urea concentration of 0.5%. Notably, irrespective of CaCO3 precipitation, the strain DW018 was able to utilize MICP to promote the attachment of Tb 3+ to its cell surface. Initially, Tb 3+ existed in amorphous form on the bacterial surface; however, upon the addition of a calcium source, Tb 3+ was encapsulated in calcite with the growth of CaCO3 at the late stage of the MICP. The recovery effect of the strain DW018 was related to the amino, hydroxyl, carboxyl, and phosphate groups on the cell surface. Overall, the MICP system is promising for the green and efficient recovery of rare earth ions from wastewaters.